COMPETENCIA PREADULTA DEPENDIENTE DE LA DENSIDAD: DROSOPHILA SUBOBSCURA CON D. SIMULANS Y D. PAVANI (DIPTERA: DROSOPHILIDAE - Budnik, Myriam; Cifuentes, Lucía (Acta Entomológica Chilena, 2022)
Preadult competition for food resources of Drosophila subobscura, D. simulans and D. pavani, under bispecific conditions but with different initial proportions of eggs of each of the species was studied. The results showed that in the three species under the competitive conditions used the viability and egg-to-adult development time varied according to the initial proportion of eggs. D. subobscura was shown to be a bad competitor with respect to D. simulans and D. pavani.